Immunopotentiator thymosin alpha-1 attenuates inflammatory pain by modulating the Wnt3a/β-catenin pathway in spinal cord. Issue 1 (8th January 2020) - Huang, Jiahua; Jiang, Huaqing; Pan, Meijun; Jiang, Yanjun; Xie, Lijin
Abstract : The mechanism of inflammatory pain involves the central nervous system (CNS) and the immune system. It is reported that immunopotentiator thymosin alpha-1 (Tα1) can reduce inflammation, protect neurons and strengthen the immune function. However, the roles of Tα1 in inflammatory pain still remain unclear. In this study, we found Tα1 can attenuate the complete Freund's adjuvant (CFA)-induced mechanical allodynia and heat hyperalgesia. Meanwhile, it reduced the upregulation of CFA-induced inflammatory mediators (interferon (IFN)-γ, tumor necrosis factor-α and brain-derived neurotrophic factor). In addition, we found the Wnt3a/β-catenin pathway was activated in spinal cord after the injection of CFA, paralleling with pain hypersensitivity. However, Tα1 reversed this status. In summary, Tα1 could attenuate inflammatory pain by modulating the Wnt3a/β-catenin pathway. It might be related to the downregulation of inflammatory mediators.